What to do about how to do: Reflections on the future direction of hospitality education and research - Conrad Lashley (Research in Hospitality Management, 2018)
Hospitality management provision in higher education in the UK is well established, though most courses are overly concerned with developing “how to do” skills in graduates. This paper argues that this “how to do” culture is reinforced by student learning needs, as well as the industrial experiences and learning preferences of staff. This “how to do” agenda is also reflected in much research output. The paper reports briefly on the 2018 Council for Hospitality Management Education (CHME) research conference, and confirms that much research is practitioner linked and overly reliant on a narrow band of research methods. A more research-active academic culture would lead to more critical thinking in research methods as well as in course delivery and assessment. The inclusion of increased social science content in hospitality management programmes would also create a scientific underpinning to these courses that engage critical thinking. Finally, the paper suggests that programmes might benefit from the deliberate inclusion of topics that are purposely not relevant to the vocational mission.